Effects of Compex as a Warm up for Glenohumeral Range of Motion - Melissa Ericson; Elizabeth R. Neil; Kenneth E. Games (Bowling Green State University, 2018)
Purpose: Research regarding proper upper extremity warm-up protocols remains inconclusive, especially for electrical stimulation methods like the Compex Sport Elite® unit. The purpose of this study is to evaluate the acute effects of a single treatment of the Compex® using the pre-warm-up protocol on glenohumeral range of motion compared to a standardized upper body ergometer (UBE) warm-up protocol. Methods: Thirty-five healthy, young adults completed the study (19 men, 16 women; age=22±2y; height=172.1±9.4cm; mass=71.3±16.1kg; right-hand dominant=28; left-hand dominant=7). Participants came to the research laboratory on two occasions, at least 48 hours apart. Participants were randomly assigned the order to complete an upper body ergometer protocol (UBE) and Compex Sport Elite®. All participants completed both intervention conditions. The UBE protocol consisted of five minutes of arm cycling at a perceived intensity of "somewhat hard" or 13 on the rating of perceived exertion scale. The Compex Sport Elite® protocol was based on manufacturer guidelines. Electrical stimulation was delivered for 25 minutes. Dominant arm passive glenohumeral internal rotation (IROT) and external rotation (EROT) ROM were measured before, immediately after, and 30 minutes after intervention. The average of three trials was used. The Global Rating of Change (GROC) scale was used after both post-intervention ROM measurements. Outcome measures were recorded by a researcher blinded to the interventions. Results: No significant interaction effect (λ=0.97; F(2,33)=0.54; p=0.59; ES=0.03) or main effects were observed for IROT. For EROT, no significant interaction effect was found (λ=0.88; F(2,33)=2.18; p=0.13; ES=0.12); however we found a main effect of time (λ=0.77; F(2,33)=5.03; p=0.12; ES=0.234). Follow-up pairwise comparisons indicated significant increase in EROT immediately post-intervention (1.508±.475; p=0.01) regardless of intervention. GROC values following dependent t-test resulted in no significant changes for either IROT or EROT (immediate post-intervention t34=0.72, p=0.48; 30 minutes post-intervention t34=0.59, p=0.56). Conclusions: No significant difference was found between the use of Compex® and UBE for warm-up of the glenohumeral joint. However, both interventions resulted in increased EROT immediately following application of intervention. Clinicians should select an intervention appropriate to meet patient goals, which may include a range of interventions or activities.